Nitrates in a catchment cleared of alien woody legumes in relation to ground water quality in the Atlantis aquifer (South Africa) - Van der Merwe, Nicolette (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MScAgric (Soil Science))--University of Stellenbosch, 2009.